Focus on JNJ-Q2, a novel fluoroquinolone, for the management of community-acquired bacterial pneumonia and acute bacterial skin and skin structure infections - Jones TM; Johnson SW; DiMondi VP; Wilson DT (Infection and Drug Resistance, 2016)
Travis M Jones,1,2 Steven W Johnson,1,3 V Paul DiMondi,1,4 Dustin T Wilson,1,2 1Department of Pharmacy Practice, College of Pharmacy and Health Sciences, Campbell University, Buies Creek, 2Department of Pharmacy, Duke University Hospital, Durham, 3Department of Pharmacy, Forsyth Medical Center, Novant Health, Winston-Salem, 4Department of Pharmacy, Durham VA Medical Center, Durham, NC, USA Abstract: JNJ-Q2 is a novel, fifth-generation fluoroquinolone that has excellent in vitro and in vivo activity against a variety of Gram-positive and Gram-negative organisms. In vitro studies indicate that JNJ-Q2 has potent activity against pathogens responsible for acute bacterial skin and skin structure infections (ABSSSI) and community-acquired bacterial pneumonia (CABP), such as Staphylococcus aureus and Streptococcus pneumoniae. JNJ-Q2 also has been shown to have a higher barrier to resistance compared to other agents in the class and it remains highly active against drug-resistant organisms, including methicillin-resistant S. aureus, ciprofloxacin-resistant methicillin-resistant S. aureus, and drug-resistant S. pneumoniae. In two Phase II studies, the efficacy of JNJ-Q2 was comparable to linezolid for ABSSSI and moxifloxacin for CABP. Furthermore, JNJ-Q2 was well tolerated, with adverse event rates similar to or less than other fluoroquinolones. With an expanded spectrum of activity and low potential for resistance, JNJ-Q2 shows promise as an effective treatment option for ABSSSI and CABP. Considering its early stage of development, the definitive role of JNJ-Q2 against these infections and its safety profile will be determined in future Phase III studies. Keywords: JNJ-Q2, fluoroquinolone, ABSSSI, CABP, MRSA